The Emerging Role of Pituitary Tumor Transforming Gene in Tumorigenesis - Tfelt-Hansen, Jacob (© 2006. Clinical Medicine & Research, 2006)
Pituitary tumor transforming gene (PTTG) is a newly discovered oncogene, and serves as a marker of malignancy grades in several forms of cancer, particularly endocrine malignancies such as pituitary adenomas. PTTG appears also to have a role in the genesis of some types of cancer. Also known as a human form of securin, PTTG is an anaphase inhibitor that prevents premature chromosome separation through inhibition of separase activity; hence, its degradation is required to start anaphase. Through this important function, PTTG participates in several key cellular events such as mitosis, cell cycle progression, DNA repair and apoptosis. The physiological importance of PTTG is indicated by the study of PTTG-null mice that have cell growth abnormalities in testis and pancreatic beta cells. Overexpression of PTTG has been observed in thyroid and colon cancers. In addition, 90% of pituitary adenomas overexpress PTTG, qualifying it as the best available marker for this disease. Although the exact mechanism is unknown, PTTG participates in the pathogenesis of various tumors, including pituitary tumors, by inducing aneuploidy and upregulating FGF-2, a potent mitogenic and angiogenic factor.Various growth factors, nuclear factors and hormones regulate PTTG expression in different tumor cells, which could be important to understand in order to obtain insight into the tumorigenic and tumor progression process. Here, we review the current knowledge of the biological and pathophysiological roles of PTTG.